2010
DOI: 10.1016/j.jpain.2010.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorder Modifies Cortical Response to Tactile Stimulation

Abstract: Individuals with temporomandibular disorder (TMD) suffer from persistent facial pain and exhibit abnormal sensitivity to tactile stimulation. To better understand the pathophysiological mechanisms underlying TMD, we investigated cortical correlates of this abnormal sensitivity to touch. Using functional magnetic resonance imaging (fMRI), we recorded cortical responses evoked by low frequency vibration of the index finger in subjects with TMD and in healthy controls (HC). Distinct subregions of contralateral SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 72 publications
2
51
0
Order By: Relevance
“…Central processing of innocuous stimulation was found to be abnormal in patients with idiopathic pain disorders who perceive tactile, pressure, heat, and auditory innocuous stimuli as more intense than healthy controls . One interpretation of the association between persistent pain and abnormal sensitivity to innocuous stimuli is a balance disruption between central noxious and non‐noxious processing, expressed by increased magnitude and abnormal topography of cortical innocuous processing .…”
Section: Discussionmentioning
confidence: 99%
“…Central processing of innocuous stimulation was found to be abnormal in patients with idiopathic pain disorders who perceive tactile, pressure, heat, and auditory innocuous stimuli as more intense than healthy controls . One interpretation of the association between persistent pain and abnormal sensitivity to innocuous stimuli is a balance disruption between central noxious and non‐noxious processing, expressed by increased magnitude and abnormal topography of cortical innocuous processing .…”
Section: Discussionmentioning
confidence: 99%
“…The fMRI study used 4s-duration vibrotactile flutter stimuli with 400 ÎŒm amplitude delivered at 26 Hz, stimulus parameters allowing comparison to optical imaging results in squirrel monkeys [133]. Ratings suggest that a group of 13 TMD patients perceived this flutter stimulus to be more intense than controls.…”
Section: Neuroimaging Of Brain Activity Evoked By Non-painful Stimulamentioning
confidence: 99%
“…Some more recent studies have consistently indicated generalised disturbances in somatosensory function in different subsets of TMD patients (e.g. 64,126,[218][219][220][221][222][223][224].…”
Section: Influence Of Oro-facial Pain Conditionsmentioning
confidence: 99%